Development of Information Literacy Competence in Primary School Students Through Podcast Program: an Epistemological Study - Lestiarini, Yeni; Ardy Wiyani, Novan (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Information literacy becomes increasingly crucial in the digital era, where students are required to be able to search, evaluate and utilize information effectively. This research aims to explore the potential of podcast programs in developing information literacy competencies in elementary school students by adopting an epistemological perspective. This research uses a qualitative approach with a case study method. The research subjects were students in grades 4-6 at an elementary school. Data was collected through observation, interviews, and analysis of student-produced podcast content. Data analysis was carried out using an information literacy competency framework and an epistemological perspective. The research results show that podcast programs can be an effective medium for developing students' information literacy competencies. Through the podcast production process, students are trained to search for relevant information, evaluate information sources, and present information creatively. Additionally, podcasts also encourage students to think critically and build a deeper understanding of a topic. Epistemologically, podcast programs can help students build more constructive and authentic knowledge. Students not only receive information passively, but are also actively involved in the knowledge construction process. Podcasts also allow students to share knowledge and perspectives with peers, thereby enriching their understanding. This research contributes to the development of a podcast media-based information literacy learning program. The results of this research can also be a reference for educators and curriculum developers in designing learning activities that are relevant to students' needs in the digital era.